Kontribusi Ekonomi Digital Terhadap Pertumbuhan Ekonomi Lokal - Armanusa, Armanusa; ., Masyitah; Aliah, Nurul; Mahdani, Rimal; Soufyan, Dara Angreka (Yayasan Sagita Akademia Maju, 2025)
This study analyzes the contribution of the digital economy to local economic growth at the provincial level in Indonesia in 2024. The digital economy is measured using the Indonesia Digital Competitiveness Index score, while local economic growth is represented by Gross Regional Domestic Product per capita. This study also controls for two additional variables, which are capital expenditure and employee expenditure, to isolate the influence of the digital economy. The data used is secondary data from 38 provinces, analyzed using multiple linear regression. The results of the study show that the digital competitiveness score has a positive and significant influence on local economic growth. Provinces with higher digital scores tend to have higher GDP per capita. Employee expenditure also had a positive and significant effect, while capital expenditure showed no significant impact. In summary, the digital economy has proven to play a crucial role in driving local economic growth in Indonesia. Enhancing digital competitiveness and strengthening human resource capacity are relevant strategies for accelerating equitable development. This study recommends that local governments prioritize investments in digital infrastructure and digital skill development to support inclusive economic growth.